The Role of Pump Amplitude on the Spatial Modes of Bright Squeezed Vacuum: Characterizing the Evolution of the Schmidt Modes - Amooei, Mahtab (Université d'Ottawa / University of Ottawa, 2023)
Spontaneous parametric down-conversion (SPDC) is a nonlinear optical process in which an incident field known as the pump interacts with a nonlinear crystal to produce two output fields known as signal and idler. Due to the conservation of energy and momentum, these output fields are entangled in the temporal and spatial degrees of freedom. The gain, which represents the strength of the interaction, increases in direct proportion to the strength of the pump field. In the low-gain regime, the generated field is an entangled two-photon state. This regime continues to be routinely employed in fundamental quantum optics experiments and quantum technologies. In the high-gain regime, the generated field is a multiphoton entangled state known as a bright squeezed vacuum. The goal of this thesis is to theoretically and experimentally characterize the spatial correlations present in high-gain SPDC. In order to characterize the spatial correlations between the generated fields, we utilize the Schmidt decomposition formalism. In this study, we examine the evolution of the Schmidt modes and spectrum with increasing pump amplitude. Our work shows that the Schmidt modes expand marginally in size, and the Schmidt spectrum narrows with respect to increasing gain. The narrowing of the Schmidt spectrum, as quantified by a decrease in the Schmidt number, indicates a gradual decrease in spatial entanglement.
Keywords: Quantum entanglement; Parametric down conversion; Spatial correlation; gain